The endocytic adaptor AP-2 maintains Purkinje cell function by balancing cerebellar parallel and climbing fiber synapses - Marianna Tolve; Janine Tutas; Ebru Özer-Yildiz; Ines Klein; Anne Petzold; Veronika J. Fritz; Melina Overhoff; Quinn Silverman; Ellie Koletsou; Filip Liebsch; Guenter Schwarz; Tatiana Korotkova; et al. (Cell Reports)
Summary: The loss of cerebellar Purkinje cells is a hallmark of neurodegenerative movement disorders, but the mechanisms remain enigmatic. We show that endocytic adaptor protein complex 2 (AP-2) is crucial for Purkinje cell survival. Using mouse genetics, viral tracing, calcium imaging, and kinematic analysis, we demonstrate that loss of the AP-2 μ subunit in Purkinje cells leads to early-onset ataxia and progressive degeneration. Synaptic dysfunction, marked by an overrepresentation of parallel fibers (PFs) over climbing fibers (CFs), precedes Purkinje cell loss. Mechanistically, AP-2 interacts with the PF-enriched protein GRID2IP, and its loss triggers GRID2IP degradation and glutamate δ2 receptor (GLURδ2) accumulation, leading to an excess of PFs while CFs are reduced. The overrepresentation of PFs increases Purkinje cell network activity, which is mitigated by enhancing glutamate clearance with ceftriaxone. These findings highlight the role of AP-2 in regulating GRID2IP levels in Purkinje cells to maintain PF-CF synaptic balance and prevent motor dysfunction.